Angiosarcoma with Pulmonary Metastasis Presenting with Spontaneous Bilateral Pneumothorax in an Elderly Man - Wei Chen; Chih-Shiun Shih; Yao-Tung Wang; Guan-Chin Tseng; Wu-Huei Hsu (Journal of the Formosan Medical Association, 2006)
Cutaneous angiosarcoma is a rare and invasive endothelial-derived sarcoma that occurs most frequently in the scalp and facial skin of elderly men. It is frequently accompanied by thin-walled cavitary pulmonary metastasis, and is often obscure on chest radiograph. We report a case of angiosarcoma of the scalp with cystic metastasis to the lung in a 63-year-old man, presenting as recurrent bilateral spontaneous pneumothorax. Lung metastasis was missed at the first episode of pneumothorax because the lung-expanded chest radiograph showed no significant abnormality. Two months later, bilateral pneumothorax recurred, and high-resolution computed tomography revealed multiple cystic, cavitary and nodular lesions. Pulmonary metastasis was confirmed by video-assisted thoracoscopic surgery, and pleurodesis was performed. After the operation, the patient received chemotherapy; no recurrence of pneumothorax was found during 6 months of follow-up. Pneumothorax in the elderly should be differentiated from malignant metastatic lung tumors.